Effect of storage time of Albizia lebbeck (L.) Benth. seeds on the germinative capacity - Navarro, Marlen; Febles, Gustavo; Torres, Verena; Herrera, R. S.; Noda, Aida (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the storage effect of A. lebbeck seeds on the viability, germination and dormancy indicators, a completely randomized design with factorial arrangement (3 x 6) was used, in which the factors were determined by the study years and storage times. A variance analysis was performed, according to simple classification model in factorial arrangement. The multiple comparison Duncan test (1955) was applied and differences were declared as significant at P <0.05. The percentage of viable seeds slightly decreased, as the storage increased. The most marked decrease occurred in the range of 0 to 2 months of storage started (mss) for three years, with significant differences between both evaluations in each year. Germination had variable performance in each year. In each storage period, the highest percentage, although without differ each other, it was found at 0 mss. In each of the months there were no significant differences between years, except for the value reported at 7 mss for years 1 and 3.The first year (31.0%) was not different from year 2 (34.0%), and in turn the latter showed no differences with regard to year 3 (37.75%). At the start of storage (0 mss), the values of dormant and hard seeds were identical (52.85%), although, from this evaluation slight differences were observed, which only at 11 mss were 7% (51.0 vs 58.0% respectively). It is very probably that the germination percentage and longevity of A. lebbeck seeds depend on the time they spent in the store, indicating that the intrinsic factors may be the main responsible agent of viability loss. Key words: Albizia lebbeck, germination, viability, dormancy